In vitro antibacterial activity of peruvian propolis’ ethanolic extract on Streptococcus mutans and Lactobacillus casei - Eguizábal A., Marly (2007)
With the intention of determining the antibacterial action of the ethanolic extract of Peruvian propolis (EEPP) originally from Oxapampa’s Valley (Pasco); using the method of diffusion in Plate the vine-stocks Streptococcus mutans ATCC 25175 and Lactobacillus casei ATCC 393 were used, and faced to the solutions: 0,8, 20 and 30 % v/v of the EEPP, and compared them to the witnesses Clorhexidine 0,12 % and alcohol 70 %. It was determined that the antibacterial action of the EEPP against S. mutans shows a greater tendency of inversely proportional activity in its concentration, to that of L. casei case; such antibacterial action in concentrations 0,8, 20 and 30 % is significant in comparison to the negative witness; also the action against S. mutans is greater than in L. casei; being significant in the concentrations of 0,8 and 20 %; and also the antibacterial action of the EEPP to 0,8 % is greater than the action of Clorhexidine, as much for S. mutans and L. casei. One concludes that EEPP in solution to 0,8 % has a better antibacterial action against S. mutans and L. casei that the Clorhexidine to 0,12 %.